Anti-NMDA-R autoinmune encephalitis in times of COVID-19 - Bazalar, Giuliana (2023)
A 19-year-old woman who started with respiratory symptoms and later presented subacute symptoms with behavioral and neurological disorder associated with hallucinations, aggressiveness, mutism, epileptic seizures, facial dyskinesias and fever. MRI was normal, EEG recorded delta waves, CSF and serum studies were negative for secondary causes. Treatment was initiated with acyclovir, anticonvulsants and, subsequently, she received methylprednisolone with immunoglobulin without satisfactory response. Treatment with rituximab was started, with a favorable response. The CSF panel was positive for NMDAr. It is important to recognize early the neuropsychiatric manifestations of this pathology for an opportune management having a positive impact on the long term prognosis.